Tuberculosis and chronic respiratory disease: a systematic review - Byrne, Anthony L.; Marais, Ben J.; Mitnick, Carole D.; Lecca, Leonid; Marks, Guy B. (International journal of infectious diseases, 2015)
•We performed a systematic literature review to assess the association between a history of tuberculosis and chronic respiratory disease.•Overall there was a significant association between the presence of chronic obstructive pulmonary disease or bronchiectasis and a history of tuberculosis from a total of 11 studies.•The pooled odds ratio was 3.05 (95% confidence interval 2.42, 3.85) using the DerSimonian and Laird random effects model of meta-analysis.•The strongest associations were found in countries with a high incidence of tuberculosis, as well as among “never smokers” and younger people.•In tuberculosis endemic areas, tuberculosis is strongly associated with the presence of chronic respiratory disease in adults. Chronic respiratory disease causes substantial global morbidity and mortality. The contribution of pulmonary tuberculosis to the aetiology of chronic respiratory disease is rarely considered, but may be important in tuberculosis-endemic areas. We performed a systematic literature review to assess the association between a history of tuberculosis and the presence of chronic obstructive pulmonary disease (COPD) or chronic suppurative lung disease (bronchiectasis). Study quality was evaluated using the National Heart Lung and Blood Institute quality assessment tool. Meta-analysis was performed using the DerSimonian and Laird random effects model. We identified 9 eligible studies for COPD and 2 for bronchiectasis. Overall, there was a significant association between a history of tuberculosis and the presence of COPD in adults aged over 40 years (pooled odds ratio 3.05 (95% confidence interval 2.42, 3.85). Among individual COPD studies the strongest associations were found in countries with a high incidence of tuberculosis, as well as among never smokers and younger people. In tuberculosis endemic areas, tuberculosis is strongly associated with the presence of chronic respiratory disease in adults. Efforts to improve long-term lung health should be part of tuberculosis care.